Healthy behavior during pregnancy: Scoping review - Yasmin, Yasmin; Suryaningsih, Endang Koni (Universitas Aisyiyah Yogyakarta, 2025)
Background:Maternal-fetal attachment (MFA) refers to the emotional bond or attachment that a mother has with her unborn child during pregnancy. Health behavior during pregnancy includes nutrition, personal hygiene, clothing, and stress management. Health in pregnant women to get a healthy mother and child is done while the mother is pregnant. Objective: to map the existing evidence on maternal-fetal attachment and healthy living behavior during pregnancy with a scoping review approach. Methods: using databases namely Pubmed, Science Direct, Wiley, EBSCO published between 2014-2023. Result: there are 580 articles obtained from several databases, then filtered into 4 relevant articles. Obtained from several countries, namely, Finland 1 article, America 1 article, Iran 1 article, and Rhode Island with a total of q articles. Of the 4 articles, 2 articles were obtained that used a cross-sectional design, namely in articles A3 and A4, then for articles with a cohort-study design, namely A1, while articles that used qualitative research were A2. Conclusion: there are several influences of maternal-fetal attachment for healthy behavior during pregnancy. Some health practices that can support pregnant women are avoiding alcohol consumption, quitting smoking, exercising, conducting regular pregnancy checks.